Le ‘fantasme robotique’ du couple idéal - Nathanaël Wadbled (Recherches Germaniques)
The first season of the TV series Äkta Människor (Real Humans, 100 % humain) presents various types of emotional and sexual links between human beings and robots, raising both anthropological and social questions as to the definition of man as a relational and embodied entity. The series announces possible relationships between human beings and robots endowed with intelligence and feelings. It thus stands in opposition to the idea of the necessary sexual and emotional instrumentalization of robots because of their mechanical nature. By contrast, it describes the emergence of a community including both human beings and robots, despite the biological differences between these two distinct species. Attachment between them is thus both the result and the condition of a new definition of what is human, so that robots can be recognized as subjects of rights and of desire.